ANALYSIS OF HUMAN BODY MOVEMENT JUMPING AND JUMPING FROM A BIOMECHANICAL PERSPECTIVE - Norma Anggara; Sunarno Basuki; Joen Parningotan Purba (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2026)
This study aims to analyze the linear kinematic characteristics of leg muscles in two conditions of jumping and jumping locomotion as a basis for biomechanical evaluation of human movement. This study uses a descriptive quantitative approach with observational methods. The study population is students of the Physical Education Study Program, with a sample of 12 students who are volleyball athletes, and selected by purposive sampling based on certain criteria. Descriptive analysis is carried out by measuring movement by performing vertical and horizontal movements with leg muscle components analyzed using Kinovea software. The parameters analyzed include speed to reach, jump length, and jump height. In quantitative data to determine the distance of the jump by conducting a forward jump test with one leg support (standing board jump), and to determine the height of the jump with two legs support, a vertical jump measurement is carried out. The results of the descriptive analysis show a habitual pattern in jumping upwards (vertical jump) by bending the legs backward, because the composition of the sample is volleyball athletes who often take off on smashers. Then there is an increase in vertical speed and the configuration of vertical and horizontal motion thrust as the power of the leg muscles increases. The highest peak occurred when jumping at a value exceeding 0.119 meters per second. This finding suggests complex biomechanical adjustments are necessary to maintain movement efficiency and capability. Vertical leg muscle velocity can be an important indicator for evaluating locomotion patterns and detecting potential movement speed and horizontal range, potentially applicable to sports training.